IMAGINATIVE ANIMALS AS INSPIRATION IN THE CREATION OF DARK ART STYLE DIGITAL DRAWINGS - Fahmi, Hafiz Nur; Mujiyono (Universitas Negeri Semarang, 2025)
Traumatic experiences often leave a profound psychological impact due to shocking, frightening, or dangerous events that cause emotional distress in individuals. This work is a visual exploration in the form of dark art-style digital images, inspired by the personal experience of losing a father and the stories of others who have experienced similar mental suffering. The dark art style was chosen because it can emotionally represent trauma and raise awareness of mental health issues in the context of contemporary art. The resulting work is a 60 × 60 cm digital image printed on luster paper, featuring an imaginative animal in a gloomy landscape as the main subject. The visuals are developed symbolically and surrealistically through grotesque forms, anatomical deformations, and a dark, emotional atmosphere. Elements such as glowing red eyes, skulls, ruins, and spider webs were processed using an iPad, Apple Pencil, and the Procreate application. The creative process includes pre-production (research and sketching), production (digital drawing), and post-production (refining and printing). The imaginative animal in this work represents the deepest fears, lasting memories, and unseen forces in the human psyche, while the damaged setting serves as a metaphor for the abandoned psychological space. This work serves as an emotional expression and cultural reflection on trauma, as well as a critique of the lack of social empathy for psychological suffering.